2019
DOI: 10.1111/fwb.13427
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking continental natal homing in goliath catfish from the upper Amazon

Abstract: 1. Amazonian goliath catfishes are widespread in the Amazon Basin. Recently, otolith 87 Sr: 86 Sr analyses using laser ablation-multi-collector-inductively coupled plasma mass spectrometry (LA-MC-ICPMS) revealed a >8,000 km trans-Amazonian natal homing in Brachyplatystoma rousseauxii among fish caught and hatched in the largest Amazon River tributary, the upper Madeira basin. Although also suspected for fish in the upper Amazon, homing could not be demonstrated owing to less distinct environmental 87 Sr: 86 Sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 60 publications
(118 reference statements)
1
27
0
3
Order By: Relevance
“…One species, Brachyplatystoma rousseauxii , performs a trans‐Amazonian round‐trip migration of up ~12,000 km between its hatching areas in the Andean piedmont of Bolivia, Colombia, Ecuador, and Peru and its nursery in the lower Amazon and estuary in Brazil (Barthem & Goulding, 1997; Barthem et al, 2017). In this exceptional migration, most adult fish return to the geographical area (sub‐basin) where they were hatched (Duponchelle et al, 2016; Hauser et al, 2020), a process called ‘natal homing’. Intermediate migrations on the scale of hundreds of kilometres are performed by several species of the orders Siluriformes, Characiformes, and Clupeiformes, for reproductive or feeding purposes between the floodplains and river channel, headwaters, and tributaries (see synthesis by Araujo‐Lima & Ruffino, 2003; Diaz‐Sarmiento & Alvarez‐León, 2003; Figure 1).…”
Section: Diversity Of Migratory Behaviour In Amazonian Fishesmentioning
confidence: 99%
“…One species, Brachyplatystoma rousseauxii , performs a trans‐Amazonian round‐trip migration of up ~12,000 km between its hatching areas in the Andean piedmont of Bolivia, Colombia, Ecuador, and Peru and its nursery in the lower Amazon and estuary in Brazil (Barthem & Goulding, 1997; Barthem et al, 2017). In this exceptional migration, most adult fish return to the geographical area (sub‐basin) where they were hatched (Duponchelle et al, 2016; Hauser et al, 2020), a process called ‘natal homing’. Intermediate migrations on the scale of hundreds of kilometres are performed by several species of the orders Siluriformes, Characiformes, and Clupeiformes, for reproductive or feeding purposes between the floodplains and river channel, headwaters, and tributaries (see synthesis by Araujo‐Lima & Ruffino, 2003; Diaz‐Sarmiento & Alvarez‐León, 2003; Figure 1).…”
Section: Diversity Of Migratory Behaviour In Amazonian Fishesmentioning
confidence: 99%
“…Currently, one of the main problems for the sustainability of large migratory catfish fisheries in the Amazon basin is the construction and operation of hydroelectric dams along the main channels of its largest tributaries, restricting the reproductive and trophic migrations of fish species that live in or utilize the flood basin's aquatic environments as a migratory route (Gubiani et al, 2011;Winemiller et al, 2016). Recent records indicate a decrease in the amount of fish able to cross these barrages (Hauser et al, 2019), which is reflected in the decrease seen in records of fish production reported in the fishery landing sites, especially in upstream regions of these enterprises (Damme et al, 2019). This has been a direct source of harm to small-scale fisheries, which are traditionally responsible for maintaining the supply of animal protein in the riverine communities of the study area (Fearnside, 2013;Lima et al, 2017;Santos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Другим примером использования метода стал анализ динамики величин соотношений 87 Sr/ 86 Sr, Se : Ca и Sr : Ca от ядра к периферии отолита, проведенный у сома Brachyplatystoma rousseauxii р. Амазонки. Исследователи подтвердили хоминг и протяженность миграций вида на расстояние > 8000 км, что на сегодня является рекордной величиной для пресноводных рыб [Duponchelle et al, 2016;Hauser et al, 2020].…”
Section: примеры использования анализа микроэлементного состава кальцunclassified